(untitled) (Web of Teachers: Inderscience Research, 2024)
In recent years, Uzbekistan has witnessed a growing interest in diversifying its sports culture. While football and wrestling have traditionally dominated the athletic landscape, badminton is emerging as a sport with significant potential. Its accessibility, affordability, and appeal to a wide range of age groups make it an ideal candidate for widespread adoption. However, the growth of badminton in Uzbekistan has required innovative strategies, as traditional approaches have often focused on already established sports.